Role of bioactive compounds in the treatment of hepatitis: A review - Roy, Arpita; Roy, Madhura; Gacem, Amel; Datta, Shreeja; Zeyaullah, Md.; Muzammil, Khursheed; Farghaly, Thoraya A.; Abdellattif, Magda H.; Yadav, Krishna Kumar; Simal-Gandara, Jesus (Frontiers in Pharmacology, 2022)
Hepatitis is inflammation of liver in which swelling that happens when tissues of the body are injured or infected. They are of various types and detrimental for the human being. Natural products have recently been used to develop antiviral drugs against severe viral infections like viral hepatitis. They are usually extracted from herbs or plants and animals. The naturally derived compounds have demonstrated significant antiviral effects against the hepatitis virus and target various phases of the viral life cycle, viral release, replication, and its host-specific interactions. Natural products such as phenylpropanoids, flavonoids, xanthones, anthraquinones, terpenoids, alkaloids, aromatics, etc., have shown antiviral effects against hepatitis B and hepatitis C viruses. With recent studies conducted to understand the viral hepatitis life cycle, more effective naturally derived drugs are being produced with a promising future for the treatment of the infection. This review emphasizes the current strategies for treating hepatitis, their shortcomings, the properties of natural products and their numerous types, clinical trials, and future prospects as potential drugs.